Collocability of Mental Capacity Evaluative Adjectives in Current English - Evarist Bamuhiga, Bazili (Journal of Language and Literature, 2019)
The study was conducted to investigate the collocability of mental capacity evaluative adjectives in current English. In English people have been and are still describing each other. This description goes hand in hand with giving value to other people especially on the intelligence of a person. In English language, this function is fulfilled with the use of a number of devices one of which is evaluative adjectives, more specifically evaluative mental capacity adjectives. However, the understanding of the way these adjectives are used to convey a given value in a given particular context is limited. Thus the current study contributes to this limited knowledge by exploring how this device is used by looking at collocability of such adjectives. The study was guided by a major research question namely: What nouns do positive evaluative mental capacity adjectives collocate with? The study was a corpus-based study and the data were extracted from British National Corpus. The analysis is based on five positive adjectives namely bright, intelligent, sharp, clever and smart. In the analysis, both qualitative and descriptive statistics techniques were employed. The findings show that the studied adjectives collocate with nouns of particular human reference or related to human cognitive actions or parts of human body. Thus three general categories of nouns that collocate with these adjectives are common nouns, proper nouns, and pronoun.